Penanggulangan Kecanduan Game Online Melalui Pendidikan Karakter Regilius Pada Anak - Tohet, Moch; Mauliza, Sofiya (Belajea: Jurnal Pendidikan Islam, 2021)
The purpose of this study was to instill religious characters in children who are addicted to online games in Langkap village, Bringin hamlet, Besuki, Situbondo through 1) Megrib reciting movement 2) Reading shalawat nariya 3) Routine memorization 4) and showing Islamic films. The method used is a qualitative descriptive approach. This research was conducted in Langkap Village, Bringin Hamlet, Besuki, Situbondo. The subjects in the study, namely parents, village officials, and children who are addicted to online games. This research was conducted so that children who are addicted to online games can be overcome and their dependence on online games can be minimized and as a form of gratitude and love for Allah SWT and the Prophet SAW. The implication in overcoming addiction to online games through religious character education is one of the positive impacts for children, namely that children are not constantly fixated on online games, and make children tend to do things that are more useful and have a better personality than before.